Notch sensitivity study in u-notched polymers built by Additive Manufacturing (AM) - Jorge Guillermo Daz Rodrguez; Alberto David Pertuz Comas; Juan David Sandoval Herrera (Fracture and Structural Integrity)
Onyx is a new material composed of Polyamide 6 reinforced with short carbon fiber, used in the novel additive manufacturing composites technique. This paper aims to presents the axial fatigue performance of this material with and without U-notches. The experimentally determined S-N fatigue curve was obtained under axial load with a load inversion ratio, R = 0.1, and compared to fatigue performance of U-notched samples ranging from 0.25 to 2 mm radius. In addition, the stress concentration factor was compared for static and alternative loading to obtain the notch sensitivity in terms of the U-notch radius, showing that there is indeed a difference in stress concentration between them. The advantage of the approach is that it permits using commonly used dimensioning methods for this AM material.